Second and fourth (2D:4D) digit ratio in heroin and cannabis addicted patients - Gurok, Mehmet Gurkan; Yildiz, Sevler; Aksoy, Dilek Bakis; Kilicaslan, Asli Kazgan; Tabara, Muhammed Fatih; Yilmaz, Tuba; Atmaca, Murad (Routledge Journals, Taylor & Francis Ltd, 2025)
The etiology of addiction has not yet been fully elucidated. The ratio between the length of the second and fourth fingers (2D:4D ratio) has been linked with prenatal androgen concentrations, but also with addictive behvaiors. Aim: The present study aimed to evaluate the differences of 2D:4D ratio of individuals with cannabis and heroin addiction by examining them together with the control group. A total of sixty two male patients (33 opiate use disorder and 29 cannabis use disorder) with substance use disorder and the twenty-nine healthy controls were included in the present investigation. We obtained the lengths of 2D and 4D of the subjects by using sensitive calipers and calculated the 2D:4D. Heroin-addicted patients had lower 2D:4D ratio in in the right hand (significant difference between control group) (p < 0.001), there was no significant difference found between heroin-cannabis (p = 0.242) and control-cannabis 2D:4D ratios (p < 0.06). In the left hand, it was significant between the heroin-control groups (p < 0.037) and the cannabis-control groups (p < 0.023), while it was not significant between the heroin-cannabis groups (p = 1). In conclusion, we suggest that heroin-and cannabis addicted patients seem to have a lower ratio of 2D:4D compared to healthy control subjects. Our findings can be considered promising as to whether prenatal hormonal factors are important in the etiopathogenesis of addiction.
Keywords: Digit ratio; heroin; cannabis; addiction; 2D:4D